Maternal Prolactin Inhibition During Lactation is Associated to Renal Dysfunction in their Adult Rat Offspring - Passos, M.A.R. F.; Passos, M.C. F.; Oliveira, E.; Trotta, P. A.; Nogueira-Neto, J. F.; Bonomo, I. T.; Lisboa, P. C.; de Moura, E. G. (Hormone and Metabolic Research, 2011)
The renal function of rats whose mothers had hypoprolactinemia at the end of lactation was evaluated during development. Lactating Wistar rats were treated with bromocriptine (BRO, 1 mg twice a day, s.c.) or saline on days 19, 20, and 21 of lactation, and their male offspring were followed from weaning until 180 days old. 1 rat from each of the 12 litters/group was evaluated at 2 time points (90 and 180 days). Body and kidney weights, sodium, potassium, and creatinine were measured. Values were considered significant when p<0.05. Adult BRO-treated offspring presented higher body weight (+10%), lower relative renal weight at 90 and 180 days (−9.2% and −15.7%, respectively), glomerulosclerosis, and peritubular fibrosis. At 90 and 180 days, creatinine clearance was lower (−32% and −30%, respectively), whereas serum potassium was higher (+19% and +29%, respectively), but there were no changes in serum sodium. At 180 days, higher proteinuria (+36%) and serum creatinine levels (+20%) were detected. Our data suggest that prolactin inhibition during late lactation programs renal function damage in adult offspring that develops gradually, first affecting the creatinine clearance and potassium serum levels with further development of hyperproteinuria and higher serum creatinine, without affecting sodium. Thus, precocious weaning programs some components of the metabolic syndrome, which can be a risk factor for further development of kidney disease.
Keywords: prolactin; lactation; kidney function; programming